MENGEMBANGKAN SIKAP SELF LOVE MELALUI KONTEN MEDIA SOSIAL TERHADAP MENTALITAS KALANGAN REMAJA - Yenti Arsini; Alifah Dini; sa, Nerisa (Pusat Riset dan Inovasi Nasional, 2023)
Nowadays social media offers a variety of content for entertainment and others. One form of content that is widely presented is the theme of self love. Self-love which means loving yourself is a form of appreciating and creating happiness in oneself without worrying about other people's talk. But not all self-love is interpreted wisely by young people or adolescents. They interpret self-love in the form of staying in place, not improving themselves for the better, and making criticism as something to ignore under the pretext of self-love. The different meanings taken by young people make them mentally vulnerable and fragile. So that young people seem not to have the mental steel to face the world because they are trapped in self-love in the wrong meaning. For this reason, it needs to be straightened out that self-love must actually be able to make you more developed yourself, do your best, but make you at the top instead of staying in place.